"Use Me as Your Test!": Patients, Practitioners, and the Commensurability of Virtue. - Hsiung, Hansun (Osiris, 2022)
Cutting deeply into a patient's body posed a problem for medical deontology in premodern East Asia, defined by the Confucian virtue of "humaneness" and a preference for noninvasive cures. How did Japanese physicians reconcile "humaneness" with their interest in invasive European surgical techniques? This essay offers answers through the tale of Kan (1743–1804) and her physician, Hanaoka Seishū (1760–1835). Inspired by the writings of the German physician Lorenz Heister (1683–1758), Hanaoka attempted to remove a cancerous tumor from Kan's breast in 1803—the first reliably documented operation of its kind in East Asia. In the process, Hanaoka outlined a new reasoning by which the testing of un tested foreign techniques could be construed as "humane." While scholarship on the translation of European medicine in East Asia has focused on epistemic shifts, I argue that translation was also about the renegotiation of ethical relations, reconfiguring patient-practitioner roles and boundaries of the morally permissible.